miR-135b: An emerging player in cardio-cerebrovascular diseases - Yingchun Shao; Jiazhen Xu; Wujun Chen; Minglu Hao; Xinlin Liu; Renshuai Zhang; Yanhong Wang; Yinying Dong (Journal of Pharmaceutical Analysis, 2024)
miR-135 is a highly conserved miRNA in mammals and includes miR-135a and miR-135b. Recent studies have shown that miR-135b is a key regulatory factor in cardio-cerebrovascular diseases. It is involved in regulating the pathological process of myocardial infarction, myocardial ischemia/reperfusion injury, cardiac hypertrophy, atrial fibrillation, diabetic cardiomyopathy, atherosclerosis, pulmonary hypertension, cerebral ischemia/reperfusion injury, Parkinson's disease, and Alzheimer's disease. Obviously, miR-135b is an emerging player in cardio-cerebrovascular diseases and is expected to be an important target for the treatment of cardio-cerebrovascular diseases. However, the crucial role of miR-135b in cardio-cerebrovascular diseases and its underlying mechanism of action has not been reviewed. Therefore, in this review, we aimed to comprehensively summarize the role of miR-135b and the signaling pathway mediated by miR-135b in cardio-cerebrovascular diseases. Drugs targeting miR-135b for the treatment of diseases and related patents, highlighting the importance of this target and its utility as a therapeutic target for cardio-cerebrovascular diseases, have been discussed.